Power Efficient Load Balancing Algorithm in LTE-A Heterogenous Network Based on Assignment Model - Kai Liu; Jianye Zhao; Zhimin Liu (Dianxin kexue)
Energy consumption of wireless network is receiving more and more attention and has become one of key aspects of 5G while few researches on heterogeneous network （HetNet）load balancing focused in power consumption. User power model was built towards assignment model, based on which the augmented assign algorithm was proposed to minimize power of HetNet on condition of limited user data load. Simulation on system level platform show that power is effectively saved no matter base stations support sleep mode or not, meanwhile, ensure data rate of users.